STATE POLICY AND FINANCIAL SUPPORT FOR THE DEVELOPMENT OF THE UKRAINIAN AGRARIAN ECONOMY - Nataliia Maslak; Alina Brychko; Oleksandr Maslak; Svitlana Lukash (Public Policy and Administration, 2021)
This article examines the current situation in the agricultural sector of Ukraine, its impact on the economy, and opportunities for its development through the use of state policy and financial support. Various programs and projects have been initiated and implemented in this direction. These programs aim at encouraging the development of various agricultural activities as well as the development of the processing and logistics industries, which will lead to the increased production and export of Ukrainian agricultural products. The purpose of this article is to determine the main directions of state regulation and development of the Ukrainian agrarian economy, taking into account the implementation of sectoral government programs and the global market conditions. The object of this article is the organisational and economic mechanism for the functioning, development, state regulation, and financial support of the Ukrainian agrarian economy. The practical significance of the obtained results is to substantiate the directions of development of the agrarian economy of Ukraine for increasing the efficiency of its functioning. This article reveals the theoretical and scientific-methodological foundations of state regulation of the agricultural market. The peculiarities of the functioning and development of the regional market were determined, and both the state of the grain economy of Ukraine and the mechanism of its regulation were analysed. Based on this, conclusions and proposals were made for the development of the agricultural economy of the region and the state regulation of the agricultural market on the basis of business processes.